A Novel Creatinine-Based Equation to Estimate Glomerular Filtration Rate in Chinese Population With Chronic Kidney Disease: Implications for DOACs Dosing in Atrial Fibrillation Patients - Zhou, Ling-Yun; Yin, Wen-Jun; Zhao, Jun; Zhang, Bi-Kui; Hu, Can; Liu, Kun; Wang, Jiang-Lin; Zhou, Ge; Chen, Lin-Hua; Zuo, Shan-Ru; Xie, Yue-Liang; Zuo, Xiao-Cong (Frontiers in Pharmacology, 2021)
Background: Over/under-estimating renal function may increase inappropriate dosing strategy associated adverse outcomes; however, previously reported equations to estimate renal function have limited accuracy in chronic kidney disease(CKD) patients. Consequently, we intended to develop a novel equation to precisely estimate renal function and subsequently guide clinical treatment for CKD patients. Methods: A novel approach, Xiangya-s equation, to estimate renal function for CKD patients was derived by linear regression analysis and validated in 1885 patients with measured glomerular filtration rate(mGFR)<60ml/min/1.73m2 by renal dynamic imaging at 3 representative hospitals in China, with the performance evaluated by accuracy, bias and precision. In the meanwhile, 2165 atrial fibrillation(AF) patients who initiated direct oral anticoagulants(DOACs) between December 2015 and December 2018 were identified and renal function was assessed by estimated creatinine clearance(eCrCl). Events per 100 patient-years was calculated. Cox proportional hazards regression was applied to compare the incidence of outcomes of each group. Results: Xiangya-s equation demonstrated higher accuracy, lower bias and improved precision when compared with 12 creatinine-based and 2 CysC-based reported equations to estimate GFR in multi-ethnic Chinese CKD patients. When we applied Xiangya-s equation to patients with AF and CKD prescribed DOACs, wide variability was discovered in eCrCl calculated by the Cockcroft-Gault(CG), Modiﬁcation of Diet in Renal Disease Study(MDRD), Chronic Kidney Disease Epidemiology Collaboration(CKD-EPI), Xiangya equation which we had developed for generally patients and Xiangya-s equations, which persisted after grouping by different renal function stages. Equation choice affected drug-dosing adjustments, with the formulas agreeing for only 1.19%, 5.52%, 33.22%, 26.32%, and 36.61% of potentially impacted patients for eCrCl cutoffs of <15, <30, 15-49, 30-49, ≥50ml/min, respectively. Relative to CG equation, accordance in DOACs dosage was 81.08%, 88.54%, 62.25%, and 47.68% for MDRD, CKD-EPI, Xiangya and Xiangya-s equations for patients with CrCl<50ml/min(eCrCl cutoffs of <30, 30-49, ≥50ml/min), respectively. Reclassification of renal function stages by Xiangya-s equation was significantly associated with stroke or systemic embolism, non-major clinically relevant bleeding and any bleeding events. Conclusions: Xiangya-s equation provides more accurate GFR estimates in Chinese CKD patients who need consecutive monitoring of renal function, which may assist clinicians in choosing appropriate drug dosages.